Enhancement of the modulus of compression of calcium silicate hydrates via covalent synthesis of CNT and silica fume. (20th February 2019) - Kim, G.M.; Kim, Y.K.; Kim, Y.J.; Seo, J.H.; Yang, B.J.; Lee, H.K.
Highlights: CNT and silica fume were covalently synthesized. Synthesized CNT and silica fume incorporated cement composites were fabricated. Covalently synthesized CNT and silica fume improved the stiffness of C-S-H. Covalently synthesized CNT and silica fume significantly enhanced mechanical strength. Abstract: The effects of covalently synthesized CNT and silica fume on the modulus of compression of calcium silicate hydrates were investigated in the present study. For the conjugation of CNT and silica fume, the surfaces of silica fume and CNT were functionalized with a primary amine group and a carbonyl chloride group, respectively. The aminated silica fume and carbonyl chloride functionalized CNT were covalently bonded by the formation of amide bridges. The characteristics of the covalently synthesized CNT and silica fume were investigated via zeta potential, Fourier-transform infrared spectroscopy, scanning electron microscopy, Raman spectroscopy and sedimentation tests. The compressive strength and modulus of compression of calcium silicate hydrates of cementitious composites incorporating the synthesized CNT and silica fume were then investigated. The test results showed that the addition of the synthesized CNT and silica fume improved the stiffness of calcium silicate hydrates, thereby significantly increasing the compressive strength of the composites.